Competitive Advantage and Firm Performance: Debt Financing as a Moderating Variable - Rita, Maria Rio; Hidayat, Riskin; Kristanto, Ari Budi (Department of Management, Faculty of Economics and Business, Universitas Negeri Semarang, 2022)
This study aims to examine the moderating role of debt financing in the effect of competitive ad- vantage on the performance of Lasem-Rembang batik MSMEs. Capital from debt is expected to optimize the role of competitive advantage to strengthen firm performance. The researchers used primary data through a survey of 68 batik MSME entrepreneurs who have been operating for at least 5 years. The data was processed using Partial Least Squares-Structural Equation Model (PLS)-SEM with the WarpPLS 7.0 application by including the control variable of entrepreneur education level. The findings show that competitive advantage is not proven to have a positive effect on the perfor- mance of MSMEs; on the contrary, it has a significant negative effect. Then debt financing is demon- strated to moderate the effect of competitive advantage on MSME performance. This implies that debt financing can strengthen the effect of competitive advantage on MSME performance because it produces a positive and significant effect.